Potret Peradaban Islam Era Dinasti Umayyah - Fajri, Fadlin; Daulay, Haidar Putra; Sumanti, Soliha Titin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Abstract: The Umayyad dynasty, also known as the Umayyad Caliphate, was the first Islamic caliphate after the leadership of the companions of the prophet (Khulafaur Rashidun). They reigned from 661 to 751 in the Arabian Peninsula and its environs and from 756 to 1031 in Cordova, Spain. The name of this dynasty comes from Umayyah bin ''Abd ash-Shams, grandfather of the first Umayyad Caliph Muawiyah I. A leader would be handed over to the Muslims until Hasan Bin Abi Talib finally gave orders to Muawiyyah bin Abu Sufyan, or Muawiyyah I. Research Researchers conducted a literature study by collecting literature relevant to the Umayyads' discussion through primary and secondary literature.Abstrak: Dinasti Umayyah, juga dikenal sebagai Kekhalifahan Umayyah, adalah kekhalifahan Islam pertama setelah kepemimpinan para sahabat nabi (Khulafaur Rasyidin). Mereka berkuasa dari tahun 661 sampai 751 di Jazirah Arab dan sekitarnya dan dari tahun 756 sampai 1031 di Cordova, Spanyol. Nama dinasti ini berasal dari Umayyah bin ''Abd ash-Shams, kakek dari Khalifah Bani Umayyah pertama Muawiyah I. Seorang pemimpin akan diserahkan kepada umat Islam sampai Hasan Bin Abi Thalib akhirnya memberikan perintah kepada Muawiyyah bin Abu Sufyan, atau Muawiyyah I. Di dalam penelitian Peneliti melakukan studi literatur dengan mengumpulkan literatur yang relevan dengan Pembahasan Bani Umayyah melalui literatur primer dan sekunder.